'Papaoutai'? Family memory, parental loss and Rwandan artists today. (April 2021) - Norridge, Zoe
This article explores how family framings of childhood experiences of violence shape Rwandan artistic responses to the 1994 genocide against the Tutsi. It examines work by both child survivors of genocide and Rwandans who grew up in exile. This enables consideration of the longer legacies of violence that began against the Tutsi nearly 60 years ago, alongside the more recent aftermath of genocide. While child survivor narratives frame memory as fragile, an ongoing challenge negotiated alongside the demands of daily life and remaining family relationships; returnee narratives demonstrate a stronger intergenerational historical thread, which is nevertheless complicated by the overlaying of parental memories with the younger generation's personal contact with violence. Drawing on specific examples of artistic testimony – two memoirs, a photo essay, two solo performances, a feature film and a novel – this analysis links different genres with particular framings of family memory and examines complex identities in post-genocide Rwanda.